Effects of hyperventilation on repeated pedaling sprint performance: Short vs. long intervention duration - Sakamoto, A.; Naito, H.; Chow, C.-M. (The Journal of Strength and Conditioning Research, 2018)
Previously, hyperventilation (HV)-induced respiratory alkalosis, implemented during the last 30 seconds of each 60-second recovery that separated repeated pedaling sprints, has been shown to attenuate performance decrement. The present study investigated whether the ergogenic effects of HV would hold if the HV duration was shortened or extended. Seventeen power-trained athletes performed 10 seconds × 10 sets of standing pedaling sprints on a cycle ergometer, with a 60-second interset recovery and the load (kp) set at 0.075 × body mass, under 3 breathing conditions: control, HV of 15 seconds (HVshort), and HV of 45 seconds (HVlong). Subjects breathed spontaneously during each 60-second recovery for the control condition. Under HVshort and HVlong conditions, subjects hyperventilated at 60 breaths·min-1 with near-maximum tidal volume during the last 15 or 45 seconds, respectively, of each recovery period. Peak and mean pedaling power outputs (POpeak and POmean) were documented for each sprint set to compare performance decrements between conditions. No significant condition effect or condition × time interaction was found for POpeak and POmean. The lack of ergogenic effects with HVlong may be ascribed to a complex interaction between the positive (augmented buffering effects) and negative effects of HV (decreased aerobic energy metabolism and exaggerated discomfort sensation of increased ventilatory work). For HVshort, the implemented duration may have been too short to yield positive physiological effects. A practical implication is that ergogenic effects may be impaired when HV is too short or too long, with the duration of around 30 seconds being the target for this exercise type.